Food storage temperatures monitored at retail - Eleonora Sarno; Adriano M.L. Santoro; Salvatore Ferrante; Nicola Costanzo (Italian Journal of Food Safety, 2013)
Aim of the present work is to report data concerning the maintenance of the cold chain by retail food business operators. A total of 401 refrigerators and 105 freezers from 112 retails (big, medium, small size) were monitored for display temperatures. In addition, the surface temperature of 341 stored food products was recorded. Storage temperatures were respected in the majority of retail markets, with the exception of small retails, where cold chain was not respected. Among all food samples, yogurt was stored at temperature higher than law limits. Our findings show that retailers, in particular those from small markets, are not always familiar with cold chain maintenance. In our opinion, much more attention should be paid in keeping food at cold temperature in order to ensure food safety.